Online Higher Education: An opportunity for displaced populations - Segovia-García, Nuria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In countries such as Colombia, the lack of coverage, geographical dispersion and the armed conflict have become obstacles that prevent part of the population from accessing university, perpetuating inequalities, and vulnerability. The results of this study suggest that virtual higher education can become a useful alternative to offer training opportunities to these populations if the right conditions are provided in terms of useful and current content, personalised attention, and accessible infrastructure. The conclusions reached can guide Higher Education Institutions (HEIs) in the design of quality virtual strategies.